Influence of O. Casel on X. Zubiri - Díaz Muñoz, Guillerma (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
This article represents an invitation to see X. Zubiri as a Benedictine theologian, an innovative disciple of the famous Benedictine monk O. Casel. As monks, their distinguishing characteristic is liturgical life and, as theologians, they explain theologically the main role of liturgy (Word and Sacrament) in Christian life, according to the contemporary liturgical movement. In front of intellectualism, they recover the Pauline sense of mysterion and traditio, common terms in the mystery religions, but now with a new Christological meaning.
Keywords: Xavier Zubiri; Odo Casel; philosophy; spirituality; liturgy; Benedictine